Integrative description of Paramacrobiotus bengalensis sp. nov. (Tardigrada: Eutardigrada: Macrobiotidae), a new limno-terrestrial tardigrade species from the state of West Bengal, India - Basu, Subhrangshu; Babu, Rahul; Siddique, Alfisa; Purushothaman, Jasmine (European Journal of Taxonomy, 2023)
Paramacrobiotus bengalensis sp. nov. was discovered in a moss sample collected from a tree in West Bengal, India. We describe this new species using detailed morphological and morphometric data obtained from phase contrast microscopy and scanning electron microscopy, along with molecular and phylogenetic data analyses. Due to the presence of a cap-like structure at the distal portion of egg processes, the new species showed the highest similarity with Paramacrobiotus garynahi (Kaczmarek, Michalczyk & Diduszko, 2005), Paramacrobiotus alekseevi (Tumanov, 2005), Paramacrobiotus filipi Dudziak, Stec & Michalczyk, 2020, Paramacrobiotus sagani Daza, Caicedo, Lisi & Quiroga, 2017, Paramacrobiotus vanescens (Pilato, Binda & Catanzaro, 1991) and Paramacrobiotus gadabouti Kayastha, Stec, Mioduchowska & Kaczmarek, 2023. However, it can be differentiated from them by some morphological and morphometric characteristics. The genetic data corroborated our phenotypic outcome further supporting the new species hypothesis.